Prospective Early Childhood Teachers’ Evolving Conceptions of Using a Mathematics Learning Trajectory to Guide Intentional Teaching - (:unkn) unknown (My University, 2019)
This qualitative, phenomenological study investigated how fifteen early childhood preservice teachers’ (PSTs) mathematical knowledge needed for teaching and early mathematics learning trajectory knowledge impacted the intentionality of instructional decision-making. The central research question asked: In what ways do early mathematics learning trajectories inform prospective early childhood teachers’ instructional decisions in ways that are likely to advance student learning on the subitizing trajectory? The literature review revealed numerous studies focused on the usefulness of learning trajectory knowledge on prospective elementary and inservice teachers’ mathematical knowledge for teaching, lesson planning, instruction, and assessment, but no studies were found regarding early childhood pre-service teachers’ understanding of an early mathematics learning trajectory to guide intentional instructional decision-making. A semi-structured interview protocol with stimulus texts was designed to elicit early childhood PSTs’ understanding of subitizing, the subitizing trajectory, and the influence of each on their instructional decision-making. Five themes emerged from the analysis of this data offering insights into the intentionality of early childhood PSTs’ decision-making to advance student learning: (1) demonstrates an understanding of subitizing, (2) recognizes and validates the importance of subitizing for young children, (3) articulates learning trajectory progression through dot arrangements, (4) demonstrates an awareness of the developmental nature of children’s mathematical thinking, and (5) centers instructional decisions on children’s thinking. Findings from this study suggest early childhood PSTs (a) demonstrated a keen interest in understanding children’s thinking and were capable of crafting instructional opportunities that aligned with the subitizing learning trajectory, (b) developed a complex and nuanced understanding of the subitizing trajectory, and (c) engaged in a cycle of instructional decision-making highlighting an intricate relationship between subject matter knowledge, pedagogical content knowledge, and learning trajectory knowledge.
Keywords: developmentally appropriate instruction; early childhood mathematics education; early childhood teacher education; early mathematics learning trajectory; intentional instructional decision-making; mathematical knowledge for teaching